Taxonomy and molecular phylogeny of Cryptophyceae (Cryptophyta) from cultures - Lubiana, Karoline Magalhães Ferreira (2018)
Cryptomonads are in majority autotrophic biflagellate organisms living in aquatic environments, which can be marine, brackish and freshwater. Although cells are easily reckonable at class level due to the asymmetrical shape and the gyrating swimming motion, the identification of species needs a broad morphological approach associated to molecular data. The group\'s taxonomy is confusing and controversial, due to authors\' disagreement concerning the diacritic features for taxa identification, and even the validity of the taxa. Furthermore, cryptomonads cells, many times, are diminutive and do not possess rigid structures, complicating the morphological distinction. Consequently, the knowledge of the group\'s biodiversity is very incomplete and based on very limited sampling. Accordingly, the present study aimed to enhance the knowledge of the cryptomonads species diversity maintained in cultures. We used 53 strains for the study of the phylogenetic diversity, using sequences of nuclear SSU and ITS2, and nucleomorph SSU rDNA. Six strains had their morphologies investigated by the use of light, confocal, scanning and transmission electron microscopies. As result, one new record for the Atlantic Ocean was registered, Nephroselmis viridis, a green algae genus initially described as Cryptophyceae. In addition, four new species form coastal regions of Brazil were described, Hemiselmis aquamarina, Rhodomonas iguapensis, Rhodomonas marataiama and Rhodomonas potiguaris. The first, has a new type of phycobiliprotein, Cr-PC- 564, and the others Cr-PE 545. All the new species proposed were highly supported as monophyletic lineages. Our molecular results suggest that Rhinomonas and Storeatula must be invalidated because these genera are not monophyletic and the morphological traits are not phylogenetic informative. The newly described species were also the first cryptomonads described for the marine environment of Brazil. Consequently, the present study contributed significantly to the initial knowledge of cryptomonads composition in the South Atlantic